THE EFFECT OF ENTREPRENEURSHIP ORIENTATION TOWARD MARKET ORIENTATION AND PERFORMANCE OF SONGKOK MSME IN GRESIK REGENCY - Syarifah, Ina; Mawardi, Muhammad Kholid; Iqbal, Mohammad (Accounting Department,, 2020)
ABSTRACT Purpose — This research aims to determine the effect of entrepreneurial orientation on market orientation, entrepreneurial orientation on the performance of MSMEs, and market orientation towards the performance of MSMEs.Design/methodology/approach — The object of this research is Songkok Micro Small and Medium Enterprises (MSME) in Gresik Regency.Findings — The results of this study indicate that entrepreneurial orientation has a significant effect on market orientation, entrepreneurial orientation has a significant effect on the performance of MSMEs, and market orientation has a significant effect on the performance of MSMEs.Practical Implications — The entrepreneurial movement plays a role in economic development in Indonesia. Although the number of entrepreneurs in Indonesia is still relatively low compared to other Southeast Asian countries, according to the 2015-2016 GEM Indonesia Report survey, the intention of entrepreneurship in Indonesia is high compared to Singapore, Thailand, Vietnam and Malaysia.Originality/value — This research uses a cluster sampling method involving 163 respondents and uses PLS (Partial Least Square) analysis tools with SmartPLS 3.0 software.Keywords — Orientation; Market Orientation; Performance of MSMEs